“Eu vim para a universidade, ela fica com ele” : histórias orais das alunas-mães do curso de pedagogia - Santos, Luciana Andrade (2024)
Student mothers face challenges in remaining in higher education, especially when it comes to gender equality and opportunities, highlighting the influence of social roles defined by patriarchy and established, throughout history, for the female figure. Therefore, the present study investigated the challenges experienced by mothers of the pedagogy course in reconciling motherhood and graduation on the Professor Alberto Carvalho campus. To this end, a case study was carried out, using a qualitative approach, with the student-mothers, with interviews carried out in order to collect the individual narratives of each woman. The data collected was analyzed from the perspective of Oral History (OH) and Cultural Studies, as well as from the theoretical-methodological assumptions of studies on gender and feminism. The results showed how the roles assigned to women make them invisible when accessing other social spheres. In addition to responsibilities in the private and family sphere, and, therefore, with motherhood, they are able to reconcile, even with challenges and difficulties, and for the most part without a support and financial network, with academic and professional life. The (in)visibility and secondary status of women in the private and social space impacts personal, economic and social advancement; these premises, therefore, are directly linked to a society dominated by the patriarchy system.